Advanced Imaging for the Early Diagnosis of Local Recurrence Prostate Cancer after Radical Prostatectomy. (13th March 2014) - Panebianco, Valeria; Barchetti, Flavio; Musio, Daniela; De Felice, Francesca; Proietti, Camilla; Indino, Elena Lucia; Megna, Valentina; Schillaci, Orazio; Catalano, Carlo; Tombolini, Vincenzo
Abstract : Currently the diagnosis of local recurrence of prostate cancer (PCa) after radical prostatectomy (RT) is based on the onset of biochemical failure which is defined by two consecutive values of prostate-specific antigen (PSA) higher than 0.2 ng/mL. The aim of this paper was to review the current roles of advanced imaging in the detection of locoregional recurrence. A nonsystematic literature search using the Medline and Cochrane Library databases was performed up to November 2013. Bibliographies of retrieved and review articles were also examined. Only those articles reporting complete data with clinical relevance for the present review were selected. This review article is divided into two major parts: the first one considers the role of PET/CT in the restaging of PCa after RP; the second part is intended to provide the impact of multiparametric-MRI (mp-MRI) in the depiction of locoregional recurrence. Published data indicate an emerging role for mp-MRI in the depiction of locoregional recurrence, while the performance of PET/CT still remains unclear. Moreover Mp-MRI, thanks to functional techniques, allows to distinguish between residual glandular healthy tissue, scar/fibrotic tissue, granulation tissue, and tumour recurrence and it may also be able to assess the aggressiveness of nodule recurrence.